Helping Them Decide: A Scoping Review of Interventions Used to Help Minors Understand the Concept and Process of Assent - Weisleder, Pedro (Frontiers in Pediatrics, 2020)
For adults, understanding research protocols prior to consenting to participate can be demanding. For children, that challenge is likely amplified. Yet, the participation of minors as research subjects is necessary. Otherwise, the likelihood of improving healthcare for minors now and in the future is hampered. The risk that minors could be harmed by procedures and medicines that are ill-adapted to their age-group or lack adequate scientific basis is real. It is therefore necessary to identify age-appropriate models to help minors understand the concept and process of assent. Herein is a scoping review on the concepts of assent and dissent, tools to evaluate the capacity of minors to assent, and six empirically based methods that have been used to help minors understand the process of assent. Helping minors become better decision-makers in a manner that is commensurate with their development, supports children’s prerogative to participate as human subjects in research.